Pathway to enhancing safety behavior of construction workers through subjective well-being - Liu, Qi; Zhang, Leping; Li, Yaxin (Frontiers in Public Health, 2025)
IntroductionThis study empirically examines the influence of subjective well-being on the safety behavior of construction workers. A theoretical model is constructed based on the relationships among subjective well-being, safety awareness, safety risk perception, work stress, and safety behavior.MethodsEmpirical analysis was conducted using SPSS and AMOS software on data collected from 436 valid samples to test the proposed hypotheses and model.ResultsThe results indicate that subjective well-being has a positive impact on the safety behavior of construction workers. Safety awareness significantly enhances the ability of workers to perceive safety risks. Both safety awareness and safety risk perception serve as significant mediators in the relationship between subjective well-being and safety behavior. Furthermore, work stress negatively moderates the relationship between subjective well-being and safety behavior.DiscussionThe findings underscore the importance of promoting subjective well-being to enhance safety behavior among construction workers. The mediating roles of safety awareness and risk perception, along with the moderating effect of work stress, provide a comprehensive understanding of the underlying mechanisms. These insights offer valuable implications for developing targeted interventions to improve safety outcomes in the construction industry.